COMPARATIVE PROFESSIONAL ACCOUNTANCY-AUSTRALIA . - Gibson, Robert W. (The Accounting Review, 1965)
The purpose of this article is to outline some significant changes which have occurred during this period with particular reference to the accountant's duties arising from the Companies Acts in Australia. A recent survey of members indicated that about 21 per cent of the society members are in public practice or employees in public practice, while 3,300 of the members of the Institute of Chartered Accountants are in practice. So there would be approximately 8,500 members of the various professional bodies engaged in public practice. While the majority of accountants are affiliated with one or more of these bodies there remain a number outside. In the public practice area these persons are pre-dominantly involved in certain classes of taxation return preparation, the uniform companies acts. Under the Australian Constitution the Commonwealth Parliament can legislate only on matters expressly delegated in the Constitution. The powers of the Commonwealth with respect to companies are incomplete and the framing of companies legislation has remained a matter for the States.